The Theoretical Evaluation of Propoxur Electrochemical Determination over a Conducting Polymer, Saturated With Radical Centers - Романів, Людмила Вікторівна (Analytical & Bioanalytical Electrochemistry, 2017)
The possibility of the electrochemical detection of propoxur pesticide over a conducting polymer, saturated by radical sites, was described from theoretical mechanistic point of view. The correspondent mathematical model was developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown that, despite of the effects of radical coupling, the radical sites saturated conducting polymers may serve as an efficient electrode modifier for propoxur electrochemical detection. The reaction is expected to be diffusion controlled. The oscillatory behavior in this system is possible and may be caused by surface and electrochemical reaction factors.
Keywords: Propoxur, Food safety, Electrochemical sensors, Conducting polymers, Stable steady-state